Tellurite And Fluorotellurite Glasses For Active And Passive Fibreoptic Waveguides - O'Donnell, Matthew David (2004)
Glasses systems based on TeO2-ZnO-Na2O (TZN), TeO2-WO3, and TeO2-Na2O-ZnF2 are reported here, with a number of other components added (PbO, GeO2, Nb2O5, Bi2O3, Er2O3, Yb2O3, PbF2, and ErF3).